HIDUNG ELEKTRONIK BERBASIS SENSOR GAS MOS UNTUK KARAKTERISASI KEMATANGAN BUAH KELAPA SAWIT - Minarni Shiddiq; Lentina Br Sitohang; Ikhsan Rahman Husein; Sinta Afria Ningsih; Sri Hermonica; Annisa Fadillah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The ripeness of oil palm fruits is one of the key factors for crude palm oil qualities. Recently, electronic nose systems have been developed intensively for fruit quality assessment which relates odors to ripeness levels. This study developed an electronic nose system to characterize the ripeness levels of oil palm fruits using output voltage of each sensor and fruit hardness. The system consisted of a sensor chamber and a sample chamber. The sensor chamber consisted of eight MOS gas sensor modules of MQ series. Samples were oil palm fruits taken from oil palm fresh fruit bunches (FFB) which were previously categorized traditionally into unripe, ripe, over ripe, peeled and put into the sample chamber. Some of the fruits were also used for hardness measurement. To quantify the output voltages for each sensor, integrated trapezoid areas were calculated and related to the fruit hardness values. The results showed a significant voltage difference of each sensor for the three ripeness levels. Only four out of eight sensors showed significantly higher voltages. Three sensors which can significantly differentiate the ripeness levels are MQ3, MQ5, and MQ135 which MQ135 is the best. This shows that the electronic nose is potential for oil palm fruits. Keywords: electronic nose, fruit hardness, MOS gas sensor, oil palm fruit, ripeness